Better early outcome with enteral rather than parenteral nutrition in children undergoing MAC allo-SCT. Issue 6 (December 2018) - Gonzales, F.; Bruno, B.; Alarcón Fuentes, M.; De Berranger, E.; Guimber, D.; Behal, H.; Gandemer, V.; Spiegel, A.; Sirvent, A.; Yakoub-Agha, I.; Nelken, B.; Duhamel, A.; et al.
Summary: There is no consensus on the type of nutritional support to introduce in children undergoing allogeneic stem cell transplantation (allo-SCT) after myeloablative conditioning (MAC). This retrospective, multicenter, observational study compared the early administration of enteral nutrition (EN group, n = 97) versus parenteral nutrition (PN group, n = 97) in such patients with matching for important covariates. The primary endpoint was the study of day 100 overall mortality. The early outcome at day 100 was better in EN group regarding mortality rate (1% vs. 13%; p = 0.0127), non relapse mortality (1% vs. 7%; p = 0.066), acute GVHD grades II–IV (37% vs. 54%; p = 0.0127), III–IV (18% vs. 34%; p = 0.0333) and its gut localization (16% vs. 32%; p = 0.0136). Platelet engraftment was better in EN group than in PN group for the threshold of 20 G/L (97% vs. 80% p < 0.0001) and 50 G/L (92% vs. 78%, p < 0.0001). The length of stay was shorter in EN group (28 vs. 52 days, p < 0.0001). There were no differences between the two groups regarding the polynuclear neutrophil engraftment, infection rate or mucositis occurrence. These results suggest that, in children undergoing MAC allo-SCT, PN should be reserved to the only cases when up-front EN is insufficient or impossible to perform.